2018
DOI: 10.18781/r.mex.fit.1804-5
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de Trichoderma spp. y hongos fitopatógenos sobre el crecimiento vegetal y calidad del fruto de jitomate

Abstract: <p>El objetivo de este estudio fue determinar el efecto de tres especies de <em>Trichoderma</em> cuando se aplican solas y cuando se confrontan con tres fitopatógenos, sobre el crecimiento y calidad del fruto de jitomate. El sustrato de las plantas se inoculó con <em>Trichoderma</em> spp. solas y en confrontación con <em>Alternaria solani</em>, <em>Fusarium oxysporum</em> y <em>Phytophthora infestans</em>. En planta, se determinó la altura y pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
4
0
3
Order By: Relevance
“…Similarly, Ruíz-Cisneros et al (2018), obtained tomato plants with greater root length and dry weight when different Trichoderma isolates were applied, with respect to the control treatment, and Camargo-Cepeda and Avila (2014), found a 68 % increase in root dry weight in Pisum sativum, with respect to the control treatment, after inoculating seed and soil with commercial strains of Trichoderma. For their part, Brenes-Madriz et al (2019) found the highest elongation and dry biomass of the root, after applying T. asperellumn in sweet pepper plants (Capsicum annuum L.).…”
Section: Length and Dry Biomass Of Rootsmentioning
confidence: 84%
“…Similarly, Ruíz-Cisneros et al (2018), obtained tomato plants with greater root length and dry weight when different Trichoderma isolates were applied, with respect to the control treatment, and Camargo-Cepeda and Avila (2014), found a 68 % increase in root dry weight in Pisum sativum, with respect to the control treatment, after inoculating seed and soil with commercial strains of Trichoderma. For their part, Brenes-Madriz et al (2019) found the highest elongation and dry biomass of the root, after applying T. asperellumn in sweet pepper plants (Capsicum annuum L.).…”
Section: Length and Dry Biomass Of Rootsmentioning
confidence: 84%
“…Revista Mexicana de FITOPATOLOGÍA Advance online publication, 2022 work by producing enzymes (chitinases, b-1,3 glucanases and proteases), antibiotics (6-pentyla-pyrone), volatile compounds, siderophores, and acid indole-3-acetic acid. They also promote plant growth (Michel-Aceves et al, 2004;Infante et al, 2009;Rios-Velasco et al, 2016;Ruiz-Cisneros et al, 2018;Illa et al, 2020;Yu and Luo, 2020). Another mechanism associated with Trichoderma involves chemotropism induced by the existence of a chemical gradient of amino acids and/ or sugars, recognition (physical interaction by specific binding to the host surface), penetration and finally, mycoparasitism of the host cell wall by the action of lytic enzymes.…”
Section: Mexican Journal Of Phytopathologymentioning
confidence: 99%
“…Trichoderma. Algunos biofungicidas están basados en el uso del género Trichoderma, y se consideran de alta efectividad al producir enzimas (quitinasas, b-1,3 glucanasas y proteasas), antibióticos (6-pentil-a-pirone), compuestos volátiles, sideróforos, ácido indol-3-acetico; y promover el crecimiento vegetal (Michel-Aceves et al, 2004;Infante et al, 2009;Rios-Velasco et al, 2016;Ruiz-Cisneros et al, 2018;Illa et al, 2020;Yu y Luo, 2020). Otro de sus mecanismos implica un quimiotropismo ocasionado por un gradiente químico de aminoácidos y/o azúcares, reconocimiento (interacción física por uniones específicos de superficie del huésped), penetración y finalmente, el micoparasitismo de la pared celular del huésped por la acción de enzimas líticas (Steyaert et al, 2003;Alfiky y Weisskopf, 2021).…”
Section: Mexican Journal Of Phytopathologyunclassified
“…Con respecto al rendimiento, se determinó que con TQ hubo un aumento de 13% y con TB de 23%, ambos datos con respecto a TC. Estos resultados coinciden con diferentes autores que señalan incrementos en el rendimiento de cultivos (Oliva-Ortiz et al, 2017;Ávila-Miramontes et al, 2015;Ruiz-Cisneros et al, 2018).…”
Section: Tratamientosunclassified
“…Una alternativa es la utilización de hongos del género de Trichoderma, al que se le reconoce como agente de biocontrol debido a su capacidad de antibiosis, micoparasitismo, competencia por espacio y nutrientes, así como la producción de metabolitos secundarios (Hernández-Melchor et al, 2019). La mayoría de las especies de Trichoderma poseen un crecimiento y desarrollo acelerado, pueden tolerar condiciones ambientales extremas y son capaces de parasitar, controlar y destruir hongos, nemátodos y otros fitopatógenos (Ruiz Cisneros et al, 2018), además de tolerar la presencia de agroquímicos.…”
Section: Introductionunclassified